Unique genotype-phenotype correlations within LAMA2-related limb girdle muscular dystrophy in Chinese patients - Huang, Xiuli; Tan, Dandan; Zhang, Zaiqiang; Ge, Lin; Liu, Jieyu; Ding, Juan; Yang, Haipo; Wei, Cuijie; Chang, Xingzhi; Yuan, Yun; Yan, Chuanzhu; Xiong, Hui (Frontiers in Neurology, 2023)
Background LAMA2-related limb girdle muscular dystrophy (LGMD R23) is rare. The detailed clinical phenotypes and genetic information associated with LGMD R23 are unknown. Methods We conducted a retrospective cross-sectional and longitudinal study on 19 LGMD R23 patients. Results Normal early motor development was observed in 84.2% patients. Mild orthopedic complications were observed in 42.1% patients. 36.8% patients had seizures, which is unusually frequent in LGMD. Epilepsy was eventually diagnosed in 26.3% patients. 46.7% patients presented with motor neuropathy. Genetic analysis identified 29 pathogenic variants, with missense and frameshift variants being the most common. The mutant sites were mainly distributed in the N-terminal and G-like domains of laminin. The missense variants are distributed near the N-terminus (exons 3–11), whereas frameshift variants are distributed in exons 12–65. Five patients were diagnosed with epilepsy and all of them harbor at least one missense variants in exon 4. 71.4% variants of patients with motor neuropathy located in the LN domain. Conclusions Missense variants in exon 4 maybe correlated with epilepsy and variants in the LN domain maybe correlated with motor neuropathy in Chinese patients. Our study expands the clinical and genetic spectrum caused by LAMA2 variations and provides novel genotype-phenotype correlations of LGMD R23.